The Role of Supply Chain Management toward Performance of Manufacturing Companies in Yemen - Hussein Mohammed Abu Al-Rejal; Zulkifli Mohamed Udin; Rushami Zien B Yusoff (International Journal of Supply Chain Management, 2018)
Supply chain management plays a major role in industrial companies, with strengthen collaboration among their suppliers and customers. The main aims of his paper, is to examine the role of Supply Chain Management Capabilities- SCMC toward industrial companies performance in Yemen. Top and middle managers were asked to answer the questionnaire, which drawn from a geographical clustered sample. Thirty nine manufacturing were surveyed in five governorates. To examine the role of SCMC towards industrial companies hypothesis testing employed correlation. The findings showed a significant positive relationship at statistical significant level ( 0.05) between outside-in capabilities and inside-out capabilities, inside-out capabilities and companies market performance only, and spanning capabilities with both outside-in capabilities and companys performance.